2009
DOI: 10.1103/physrevlett.102.226102
|View full text |Cite
|
Sign up to set email alerts
|

Destabilization of the Mg-H System through Elastic Constraints

Abstract: We tune the thermodynamics of hydrogen absorption in Mg by means of elastic clamping. The loading isotherms measured by hydrogenography show that Mg films covered with Mg-alloy-forming elements, such as Pd and Ni, have hydrogen plateau pressures more than 2 orders of magnitude higher than bulk Mg at the same temperature. An elastic model allows us to interpret the Mg thickness dependence of the hydrogen plateau pressure. Our results suggest an alternative route for the development of new hydrogen storage mater… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
185
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(196 citation statements)
references
References 20 publications
(27 reference statements)
10
185
1
Order By: Relevance
“…11,12 Moreover, in Mg-based multilayers, it was shown that the equilibrium pressure is modified by two orders of magnitude, when a thin film is clamped by surrounding Pd layers. 24 We find here that the annealing of Mg nanoparticles ͑prepared from gas phase synthesis͒ in vacuum at 60°C for 24 h leads to voids in the smaller nanoparticles of size ϳ15-20 nm ͓Figs. 6͑a͒ and 6͑b͔͒.…”
Section: E Annealing Of Small "<10 Nm… Mg Nanoparticlesmentioning
confidence: 63%
“…11,12 Moreover, in Mg-based multilayers, it was shown that the equilibrium pressure is modified by two orders of magnitude, when a thin film is clamped by surrounding Pd layers. 24 We find here that the annealing of Mg nanoparticles ͑prepared from gas phase synthesis͒ in vacuum at 60°C for 24 h leads to voids in the smaller nanoparticles of size ϳ15-20 nm ͓Figs. 6͑a͒ and 6͑b͔͒.…”
Section: E Annealing Of Small "<10 Nm… Mg Nanoparticlesmentioning
confidence: 63%
“…Regarding the effect of the surface layer, Baldi et al reported that Mg thin film capped with a layer of Mg alloy-forming elements increased equilibrium pressures for hydrogen absorption. 32,33) The hydrogen absorption pressure of Mg film depends on the film thickness in the investigated range of 10-40 nm. 32) These phenomena were interpreted as effects of the elastic clamping of the surface layer, which inhibits volume expansion of the Mg layer during hydrogen absorption.…”
Section: Resultsmentioning
confidence: 99%
“…The small change of ∆H in the latter two cases was probably due to the additional lattice defects introduced by doping with Fe and Pd metals. On the other hand, Baldi and coworkers showed, using hydrogenography, that it is possible to tune the thermodynamics of hydrogen absorption in Mg by means of elastic clamping [28]. They prepared the block layer 2x[Ti(10nm)/Mg(20nm)]/Pd(10nm) and proved that Pd is able to increase the hydrogen plateau pressure more than 200 times with respect to bulk Mg via the elastic constrain exerted on the expanding Mg layer.…”
Section: Pd-capped Mg Thin Filmsmentioning
confidence: 99%
“…samples deposited on glass with X = Ni, Pd, Ti, Nb, and V. The dashed line is the pressure at which coexistence of and phases begins to appear upon hydrogen absorption in bulk Mg. σx and σy are compressive stresses in the x and y direction due to the cap layer (from Ref. [28]). …”
Section: Pd-capped Mg Thin Filmsmentioning
confidence: 99%